Facile Strategies for Incorporating Chiroptical Activity into Organic Optoelectronic Devices - Lee, Hanna; Kim, Danbi; Cho, Jeong Ho; Lim, Jung Ah (AMER CHEMICAL SOC, 2025)
Conspectus Chiral optoelectronics, which utilize the unique interactions between circularly polarized (CP) light and chiral materials, open up exciting possibilities in advanced technologies. These devices can detect, emit, or manipulate light with specific polarization, enabling applications in secure communication, sensing, and data processing. A key aspect of chiral optoelectronics is the ability to generate or detect optical and electrical signals by controlling or distinguishing CP light based on its polarization direction. This capability is rooted in the selective interaction of CP light with the stereogenic (non-superimposable) molecular geometry of chiral substances, wherein the polarization of CP light aligns with the intrinsic asymmetry of the material. Among the diverse chiral materials explored for this purpose, π-conjugated molecules offer special advantages due to their tunable optoelectronic properties, efficient light？matter interactions, and cost-effective processability. Recent advancements in π-conjugated molecule research have demonstrated their ability to generate strong chiroptical responses, thereby paving the way for compact and multifunctional device designs. Building on these unique advantages, π-conjugated molecules have advanced organic electronics into rapidly evolving technological fields. The combination of chiral π-conjugated molecules with organic electronics is anticipated to simplify the fabrication of chiroptical devices, thereby lowering technical barriers and accelerating progress in chiral optoelectronics. This Account introduces strategies for incorporating chiroptical activity into organic optoelectronic devices, focusing on two main approaches: direct incorporation of chiroptical activity into π-conjugated polymer semiconductors and integration of chiral organic nanoarchitectures with conventional organic optoelectronic devices. In the first approach, we especially highlight simple methods to induce chiroptical activity in various achiral π-conjugated polymers through the transfer of chirality from small chiral molecules. This hybrid approach effectively combines the excellent electrical properties and various optical transition properties of achiral polymers with the strong chiroptical activity of small molecules. Moreover, we address a fundamental challenge in achieving chiroptical transitions in planar π-conjugated polymers, demonstrating the development of low-bandgap π-conjugated polymers that exhibit both strong chiroptical activity and excellent electrical performance. Another approach, incorporating chiroptical activity into existing organic optoelectronic devices, which have already achieved significant performance advances, presents an effective strategy for high-performance chiral optoelectronics. For this purpose, we introduce the use of supramolecular assemblies of π-conjugated molecules to impart chiroptical responses into high-performance optoelectronic systems, utilizing efficient charge transfer of photoexcited electrons in chiroptical supramolecular nanoarchitectures. Additionally, we explore the integration of organic chiral photonic structure into organic optoelectronic systems, which act as optical filters tailored for CP light. These architectures offer unique advantages, including easy processability and seamless compatibility with existing organic electronic platforms. By bridging concepts from chiral organic optoelectronic materials and advanced organic electronics, this work outlines actionable approaches for advancing chiral optoelectronic technologies. These strategies underscore the versatility of π-conjugated molecules while also expanding the framework for next-generation applications. As the field of chiral optoelectronics evolves, integrating chiroptical functionalities into organic devices will facilitate transformative innovations in quantum computing, biosensing, and photonic encryption.